Stimulasi Kemampuan Motorik Halus Anak Melalui Modifikasi Kegiatan Mengancing dan Mengikat - Juliana Juliana; Rahmah Rahmah; Swandra Rahayu (PT. Riset Press International, 2026)
This study aims to improve the fine motor skills of children aged 5-6 years at TK Negeri Bantar through 2M activities (buttoning and tying). The main problem in this research was the low hand-eye coordination of children, where in the initial condition, the